A macroscopic three-dimensional tetrapod-separated graphene-like oxygenated N-doped carbon nanosheet architecture for use in supercapacitors. Issue 25 (9th June 2016) - Chen, Can; Xu, Guobao; Wei, Xiaolin; Yang, Liwen
Abstract : A macroscopic three-dimensional tetrapod-separated graphene-like oxygenated N-doped carbon nanosheet architecture for use in supercapacitors is demonstrated. Abstract : Macroscopic three-dimensional oxygenated carbon materials with enriched nitrogen (designated as PGOCN) are prepared by a two-step solid-state pyrolysis of a mixture of urea and glucose inside a template framework of melamine sponge in a N2 atmosphere without any functionalizing or crosslinking agents. Characterization by SEM, TEM, XPS and nitrogen adsorption–desorption isotherm measurements reveals that the prepared samples consist of a tetrapod framework embedded with crumpled graphene-like oxygenated N-doped carbon nanosheets, demonstrating a hierarchical porous structure of macro-, meso- and micropores. Considering the hierarchical porous structure combined with the presence of abundant oxygen and nitrogen as well as high electrical conductivity, the application of the PGOCN materials in high-performance supercapacitors is investigated. In three-electrode systems, the PGOCN electrodes show high specific capacitances of 348 F g −1 in acidic electrolytes and 308 F g −1 in alkaline electrolytes at a current density of 1 A g −1, respectively. Remarkably, the PGOCN materials can be directly cut into thin sheets to assemble two-electrode supercapacitor devices without adding binders and conducting additives using 6 M KOH as the electrolyte. The two-electrode supercapacitor device exhibits a high specific capacitance of 220 F g −1 at 0.2 A g −1 and a power density of 1.2 kW kg −1 at an energy density of 3.4 Wh kg −1 as well as outstanding cycling stability after 2000 cycles. The facile and low-cost preparation procedure combined with excellent electrochemical performance indicates that the developed materials have great potential for applications in energy storage devices such as supercapacitors.